What do Parents of Homeschoolers Do to Improve the Well-being of their Children (Based on SDT-approach) - A.S. Strukova; K.N. Polivanova (Культурно-историческая психология)
This paper focuses on the practices that parents of homeschoolers use to support their children's well-being during the learning process. According to Self-Determination Theory (SDT), practices related to satisfying basic psychological needs (autonomy, competence, affiliation) and supporting intrinsic motivation can be considered as practices to improve the level of well-being. We used the database that was created by analyses of 39 interviews with homeschoolers' parents. The authors conclude that parents consider autonomy and intrinsic motivation to be the main focus of their attention. Parents also pay attention to satisfying the other two basic psychological needs: competence and affiliation.